A Developmental Cascade Model of Behavioral Sleep Problems and Emotional and Attentional Self-Regulation Across Early Childhood. Issue 1 (2nd January 2017) - Williams, Kate E.; Berthelsen, Donna; Walker, Sue; Nicholson, Jan M.
Abstract : This article documents the longitudinal and reciprocal relations among behavioral sleep problems and emotional and attentional self-regulation in a population sample of 4, 109 children participating in Growing Up in Australia: The Longitudinal Study of Australian Children (LSAC)–Infant Cohort . Maternal reports of children's sleep problems and self-regulation were collected at five time-points from infancy to 8–9 years of age. Longitudinal structural equation modeling supported a developmental cascade model in which sleep problems have a persistent negative effect on emotional regulation, which in turn contributes to ongoing sleep problems and poorer attentional regulation in children over time. Findings suggest that sleep behaviors are a key target for interventions that aim to improve children's self-regulatory capacities.